Pengaruh Implementasi Sistem Informasi Akuntansi dan Digitalisasi terhadap Efisiensi Operasional Perusahaan pada PT Alfascorpii Medan Cabang SM Raja - Haikal Davansyah Lubis; Frenky Situmorang; Audra Nailufar; Yonson Pane (Politeknik Ganesha Medan, 2026)
This study aims to examine the impact of the implementation of an accounting information system and digitalization on operational efficiency at PT Alfascorpii Medan. In an increasingly competitive business environment, the use of information technology has become a key factor in improving efficiency. Accounting Information Systems (AIS) improve the accuracy and speed of financial information, while digitalization helps automate and integrate operational processes. Therefore, the implementation of AIS and digitalization is an important strategy for enhancing operational efficiency. This study uses a quantitative approach, with data collected from primary and secondary sources. The sample includes all 60 employees at the Sisingamangaraja branch of PT Alfa Scorpii. Data analysis was conducted using SPSS version 26, including validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression, and hypothesis testing using t-test, F-test, and coefficient of determination (R²). The results show that partially, the implementation of AIS has a positive and significant effect on operational efficiency. Digitalization also has a positive and significant effect when considered together. Simultaneously, AIS implementation and digitalization have a positive and significant effect on operational efficiency. The Adjusted R-Square value of 0.443 indicates that these variables explain 44.3% of operational efficiency, while the remaining 55.7% is influenced by other factors outside this study.